-(5u-v-6)=

Simple and best practice solution for -(5u-v-6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(5u-v-6)= equation:


Simplifying
-1(5u + -1v + -6) = 0

Reorder the terms:
-1(-6 + 5u + -1v) = 0
(-6 * -1 + 5u * -1 + -1v * -1) = 0
(6 + -5u + 1v) = 0

Solving
6 + -5u + 1v = 0

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -5u + -6 + 1v = 0 + -6

Reorder the terms:
6 + -6 + -5u + 1v = 0 + -6

Combine like terms: 6 + -6 = 0
0 + -5u + 1v = 0 + -6
-5u + 1v = 0 + -6

Combine like terms: 0 + -6 = -6
-5u + 1v = -6

Add '-1v' to each side of the equation.
-5u + 1v + -1v = -6 + -1v

Combine like terms: 1v + -1v = 0
-5u + 0 = -6 + -1v
-5u = -6 + -1v

Divide each side by '-5'.
u = 1.2 + 0.2v

Simplifying
u = 1.2 + 0.2v

See similar equations:

| lg(x)=0.04084 | | 3a(a-2)+a=2(a+1) | | 3q/4-5=5q/8 | | f/8-1=2 | | P/6=5-2p/3 | | 8+3x+4x=10x-1 | | 9x+7=8x-12 | | 5z/6-7z/12=6 | | 5(3x-5)+2(3x+2)= | | 51+38=x | | 5z/6-7z/12 | | r(x)=3 | | 3x^2-5x-1=o | | 5-37=108 | | 4c-17=1/3(8-2c) | | 27/3=x | | 1/4(16f-4)= | | 90+90+143+x=360 | | 31-4= | | 90+90+143+x=180 | | 25-5z=15 | | e+4*2=14 | | 1/4(16f-4) | | x-23=k | | -2(7x-8)+5=14x+21 | | 80=4f+12 | | 4z/7-1=-7 | | -11=-5+3c | | 5=m/4-1 | | -4x-5y=-8 | | m=n+16 | | T=4s+3.67 |

Equations solver categories